1988
DOI: 10.1002/tera.1420380203
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of trichloroacetonitrile in the long‐evans rat

Abstract: Trichloroacetonitrile (TCAN) is among a number of contaminants found in drinking water produced by reactions of chlorine with background organic material. Long-Evans rats were intubated with TCAN (0, 1, 7.5, 15, 35, 55 mg/kg) in a tricaprylin vehicle on gestation days 6-18. The highest dose tested (55 mg/kg) was lethal in 21% of the dams and produced 100% resorptions in two-thirds of the survivors. Only one maternal death was seen at the next-lower dose; however, fetal weight and viability were decreased in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…Hunter et al (1996) observed changes in neural tube development when mouse embryos were exposed to HAAs. Several chloroacetonitrile compounds have been shown to increase the rate of resorption, to reduce fetal body weight and survival (Smith et al 1997), and to result in an increase in malformations of the cardiovascular, digestive, soft tissue, and urogenital systems (Smith et al 1988, 1989b). However, these adverse developmental effects have only been demonstrated at high doses in conjunction with severe fetotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Hunter et al (1996) observed changes in neural tube development when mouse embryos were exposed to HAAs. Several chloroacetonitrile compounds have been shown to increase the rate of resorption, to reduce fetal body weight and survival (Smith et al 1997), and to result in an increase in malformations of the cardiovascular, digestive, soft tissue, and urogenital systems (Smith et al 1988, 1989b). However, these adverse developmental effects have only been demonstrated at high doses in conjunction with severe fetotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…HANs have already shown different toxic effects such as reproductive toxicity [Smith et al, 1986[Smith et al, , 1988[Smith et al, , 1989] and inhibition of rat hepatic glutathione-S-transferases [Ahmed et al, 1989]. DBAN and DCAN were found to be able to initiate tumors in SENCAR mouse skin when applied top- ically .…”
Section: Discussionmentioning
confidence: 99%
“…'Significantly different from tricaprylin control, p ^ 0.05. "Significantly different from tricaprylin control, p <, 0.001. reduced pregnancy rate, litter résorption and early neonatal death, were made by Smith et al (1988Smith et al ( , 1989. The developmental effects of BCAN, the HAN ranked third, were further examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on pregnancy rate, litter résorption and early neonatal death, TCAN was determined to be the compound which most warranted further study; DCAN and BCAN were ranked second and third, respectively. A full teratogenic evaluation was made of TCAN by Smith et al (1988), in tricaprylin vehicle (used in the in vivo screen), and again by Christ et al (1995), in an alternate vehicle, corn oil; DCAN in tricaprylin vehicle has also been evaluated for its teratogenic potential (Smith et al 1989). We present here, the developmental and teratogenic effects of BCAN in tricaprylin vehicle in the pregnant Long-Evans rat.…”
Section: Introductionmentioning
confidence: 98%